Enterprise Architecture Implementation for Regional Tax Information Systems Using the Zachman Framework - Andika Isma; Hajar Dewantara; Salim Diarra (Global Research and Collaboration, 2025)
An effective and efficient information system in managing regional taxes is the key to increasing transparency, efficiency and service to taxpayers. In this context, this study aims to identify relevant perspectives in local tax management and analyze the appropriate use of technology to develop an effective information system. This study uses the Zachman Framework approach. The results show that the use of technologies such as databases, cloud computing, web-based applications, and system integration has the potential to increase efficiency and transparency in local tax management. However, it must be acknowledged that the implementation of this technology also has challenges such as implementation costs and the need for adequate technical expertise. In terms of development prospects, the use of appropriate information and technology systems can improve efficiency, transparency, and service in local tax management. However, further research and development is needed to overcome the challenges and maximize the potential that exists. This research provides valuable insights about the development of local tax information systems and the appropriate use of technology. The implication is increasing the efficiency of local tax management and better service to taxpayers. Overall, this research makes an important contribution to the development of local tax information systems and the use of technology in a wider context.